Análise experimental da degradação polimérica em escoamentos turbulentos com redução de arraste em uma geometria rotativa: efeitos de número de Reynolds, concentração, massa molecular, temperatura e diferentes polímeros - Pereira, Anselmo Soeiro (2012)
The drag reduction by high molecular weight polymer in a turbulent flow is an important phenomenon that has received the attention of a number of researchers in the last years. However, the efficiency of those additives is not constant. Turbulence degrades the polymer, decreasing their ability to reduce drag. Recently, this degradation phenomenon has received its deserved attention in the literature and investigations that take into account the effect of concentration, molecular weight, Reynolds number, and temperature on the physical mechanism of degradation can be found. However, these parameters have not yet been explored in very wide ranges. In the present work we investigate this degradation phenomenon using aqueous solutions of three different polymers, polyacrylamide (PAM), polyethylene oxide (PEO) and xanthan gum (XG) in a cylindrical double gap rheometer device. The dependence of degradation on molecular weight, concentration, temperature, and Reynolds number is analysed for a wide range of these parameters. Our main results are displayed in terms of drag reduction (DR). All tests are performed to compute DR for a long period of time including the values obtained from the very beginning of the process. Initially, DR presents negative values due to gain of extensional viscosity caused by polymer stretching. After reaching a minimum value, DR increases in response to the development of turbulent structures, achieving a maximum value. Finally, DR decreases as a result of polymer scissions, attaining an asymptotic value. In order to quantify the degradation, we also display the results using a relative drag reduction quantity, DR0, defined as the ratio of the current drag reduction to the maximum one obtained for a non-degraded solution. We propose an alternative decay function that relates DR0 as a function of the Reynolds number, concentration, molecular weight, and temperature